World Wide Wave of Wisdom - Culliford, Larry (2019)
Arguing that 'wisdom' may be a more acceptable and useful term than 'spirituality', this article explains the origins and hopes of a 'World Wide Wave of Wisdom' and its associated website.
Keywords: World Wide Wave of Wisdom; Spirituality; Values; Wholeness